STIRRED BIOREACTOR FOR THE ROBUSTNESS PRODUCTION OF RECOMBINANT GST.VP28 IN FED-BATCH CULTIVATION OF ESCHERICHIA COLI - MUHAMAD ALI; ISMAINI; SULAIMAN N. DEPAMEDE; BAGUS D. H. SETYONO; ALIS MUKHLIS; MUHAMAD AMIN; MOHAMMAD ASHARI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Escherichia coli is the most popular platform for the production of recombinant proteins as vaccine candidates. One important factor that may influence the quantity and quality of the expressed proteins using the bacterial host is a bioreactor. Thus, this study was aimed at comparing the influence of two different bioreactors, conventional (Sakaguchi flask) and stirred bioreactors on the growth of E. coli BL21 as a host cell and production of GST.VP28 recombinant protein in the host. The result showed that total wet biomass of E. coli BL21 harvested from the stirred bioreactor was significantly higher, compared to the total biomass from the conventional bioreactors. In addition, SDS-PAGE results also indicated that the amount of the GST.VP28 recombinant protein collected from the stirred bioreactor was higher than the quantity of recombinant protein from E. coli cultured in the conventional bioreactor. Furthermore, the stirred bioreactor also produced larger soluble fraction and lower inclusion body. This result suggested that the stirred bioreactor is very suitable for improving the production of recombinant protein using E. coli.